2013
DOI: 10.15580/gjas.2013.3.102712155
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rate and Split Application of Nitrogen Fertilizer on Yield of Two Sugarcane Varieties from Ratoon Crop

Abstract: Nitrogen fertilizers applied either in single or split application is the main agronomic inputs to sugarcane production. The objective of this study was to determine the effects of nitrogen fertilizer rates and split application on yield of first ratoon crop of late (CO 421) and early maturing (D 8484) sugarcane varieties. Analysis of variance at p≤0.05 indicated that the mean yields were 117.6 and 124.3 ton cane per hectare for CO* 421 and D* 8484 respectively at harvesting. This study showed that there was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Nitrogen mainly contributes to brix value and stem diameter. Achieng [23] study in Pakistan concluded that the soil needed 208 kg N, 53 kg P, 280 kg K, 30 kg S, 3.4 kg Fe, 1.2 kg Mn, and 0.6 Cu to produce 100 tons/ha sugarcane.…”
Section: Components Of Sugarcane Production Productivity and Sugar Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrogen mainly contributes to brix value and stem diameter. Achieng [23] study in Pakistan concluded that the soil needed 208 kg N, 53 kg P, 280 kg K, 30 kg S, 3.4 kg Fe, 1.2 kg Mn, and 0.6 Cu to produce 100 tons/ha sugarcane.…”
Section: Components Of Sugarcane Production Productivity and Sugar Yieldmentioning
confidence: 99%
“…Indonesian Sugar Research Institute mentioned that soil with very low N content requires 180 -200 kg N/ha [25]. Achien et al (2013) [23] stated that light soil requires 120 kg N/ha. Furthermore, RC1 requires twice N fertilizer application.…”
Section: Components Of Sugarcane Production Productivity and Sugar Yieldmentioning
confidence: 99%
“…Saleem et al (2012) found that N available in crop root zone is mostly depleted, necessitating the application of total required N in splits throughout the crop grand growth period. Achieng et al (2013) also carried out experiments with variable nitrogen application amounts from 0 to 180 kg ha -1 with difference of 60 kg between each rate and its splitting from 100 to 50-50 and 30-30-40 %, respectively, affecting sugarcane cultivars (CO 421 and D 8484). These results indicated that maximum cane yield was achieved with splitting of N as 30-30-40%.…”
Section: Introductionmentioning
confidence: 99%